Overcoming the Home Industry Crisis in Goyor Sarong Wanarejan Utara: Training on Digital Marketing, Product Packaging and Sales Management - Imam Ahmad Ashari; Arif Setia Sandi; Deny Nugroho Triwibowo; Irfan Arfianto; Pradestya Bima Arweina (Peneliti Teknologi Teknik Indonesia, 2023)
A crisis is currently affecting the Goyor woven sarong home industry in North Wanarejan Village (Wan-Ut), Pemalang. The Goyor sarong, which is the village's potential, is facing serious issues. The price of sarongs has plummeted, while the cost of raw materials and employee wages has soared. Furthermore, declining market demand has presented numerous challenges for sarong producers in Wan-Ut. Previously, sarong producers manufactured their products without any promotion, so a solution to address this crisis is much needed. One step that can be taken to tackle this issue is to promote the sarongs to increase market demand. Additionally, finding ways to reduce production costs is essential to improve profit margins. To achieve these goals, a community engagement program was conducted, providing training in digital marketing techniques, packaging creation, and sales management to residents of North Wanarejan Village. This program proceeded smoothly, and the residents showed great enthusiasm. Evaluation of the results was carried out directly during the program, where participants applied the sales strategie they had learned to sell Goyor sarongs online. As a result, two participants successfully sold Goyor sarongs online.